Polydioxanone vs Prolene Closure for Midline Abdominal Incisions: To Compare Postoperative Wound Dehiscence (Medical Forum Monthly, 2024)
Objectives: The objective of this study was the comparison of Polydioxanone and Prolene for midline abdominal closure in terms of postoperative wound dehiscence.Study Design: Randomized control trialPlace and Duration of Study: This study was conducted at Department of Surgery, Sheikh Khalifa Bin Zaid Al Nahyan Hospital Rawlakot Azad Kashmir from 20-12-2012 to 25-12-2014.Materials and Methods: We studied 106 patients for midline closure of abdominal surgery. We made two groups (Group A consisted patients in whom abdominal closure was done with Polydioxanone no. 1 and Group B contained patients who underwent closure with Prolene no. 1. The outcome variablewas wound dehiscence.Results: The average of age for 106 patients was 36.88 ± 13.28 years. In group A, the wound dehiscence was seen in 4 (3.8%) patients while in group B it was seen in 12 (11.3%) patients. Wound dehiscence was considerably high in group B as compared to groups A, (p-value < 0.05).Conclusion: Polydioxanone is a synthetic absorbable suture which retains its strength for longer than other absorbable materials. According to our experience Polydioxanone causes less wound dehiscence as compared to Prolene in midline abdominal wound closure.